Internalisasi Moderasi Beragama dalam Konteks Oikumene di Kampus STAKPN Sentani - Santy Layan (DIEGESIS: Jurnal Teologi Kharismatika, 2022)
This paper aims to analyze the internalization of religious moderation values using the ecumenical approach at the STAKPN Sentani campus. This research uses a qualitative approach with a case study method. Researchers used an approach of in-depth interviews, observations, and documentation studies for data collection in this study. The research found that the internalization of moderation values for students in the STAKPN Sentani environment, which is different denominations and Church doctrines, was successfully carried out by campus residents, so that harmonization, togetherness, and responsibility in caring for life together remained intertwined until this moment. Several perspectives have been considered in religious moderation from an ecumenical point of view among students to ensure that no divisions among doctrines or traditions have been held. The conclusion that can be drawn is that ecumenism is the choice of path used to connect Christians in all aspects, including denominations, doctrines, and common ideals for proclaiming the gospel. Through the internalization of moderation values for students in STAKPN Sentani environments of different denominations and doctrines the Church can take care of harmonization, unity, togetherness, and shared responsibility in arranging life together according to God's will.Keywords: STAKPN Sentani students; religious moderation; EcumeneÂ AbstrakPenulisan ini bertujuan menganalisis internalisasi nilai-nilai moderasi beragama menggunakan pendekatan oikumene di kampus STAKPN Sentani. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Peneliti menggunakan pendekatan yaitu wawancara mendalam, observasi, dan studi dokumentasi untuk pengumpulan data dalam penelitian ini. Penelitian menemukan, internalisasi nilai-nilai moderasi bagi mahasiswa di lingkungan STAKPN Sentani yang berbeda denominasi dan doktrin Gereja berhasil dilakukan oleh warga kampus, sehingga harmonisasi, kebersamaan, dan tanggung jawab dalam merawat hidup bersama tetap terjalin sampai detik ini. Beberapa perspektif telah dipertimbangkan dalam moderasi agama dari sudut pandang oikumene di kalangan mahasiswa untuk memastikan bahwa tidak ada perpecahan di antara doktrin atau aliran yang telah dipegang. Kesimpulan yang dapat ditarik adalah oikumene menjadi pilihan jalan yang digunakan untuk menghubungkan umat Kristiani dalam segala aspek, termasuk denominasi, doktrin, dan cita-cita bersama untuk mewartakan injil. Melalui internalisasi nilai-nilai moderasi bagi mahasiswa di lingkungan STAKPN Sentani yang berbeda denominasi dan doktrin Gereja dapat merawat harmonisasi, persatuan, kebersamaan, dan tanggung jawab bersama dalam menata hidup bersama sesuai kehendak Tuhan.Kata kunci: mahasiswa STAKPN Sentani; moderasi beragama; oikumene